Transition Economics : Two Decades On. - Turley, Gerard (Taylor and Francis, 2012)
Celebrating twenty years of transition from socialism to capitalism, this book is designed to be the core textbook for undergraduate courses in transition economics and comparative economic systems. Given the passage of time, Transition Economics: Two Decades On reviews and accounts for the outcomes in the so-called transition economies and, from an academic perspective, takes the reader through developments and issues in the twenty years of transition from plan to market. Treating its subject matter thematically, the book incorporates much of the transition economics literature and evidence that have evolved over the past two decades. In particular, the authors focus on the most important aspects of economic transition, including: the initial conditions at the outset of transition paradigms and patterns of transition the main transition policies and economic reforms the performance of transition countries and firms the lessons from transition. The textbook covers a wide range of both contemporary microeconomic and macroeconomic issues, in over thirty ex-socialist European and Asian countries, including Russia and China. Transition Economics: Two Decades On is more than just a book about a particular part of the world or the transformation that was experienced at a particular time in history. The authors believe that the study of the economics of transition gives the reader an insight into theories, policies, reforms, legacies, institutions, processes and lessons that have application and relevance, beyond the specific transition from plan to market, to other parts of the world and to other times in history.